Human Factors as both the Embodiment of and Potential Solution to a Broken System of Science. (September 2014) - Brill, J. Christopher; Lawson, Ben D.; Durso, Francis T.; Hancock, Peter A.; Shappell, Scott
The objective of this panel was to discuss issues critical to the modern practice of science, with a specific focus on how we train students to operate within a system that often slows scientific innovation. Chris Brill provided opening remarks to frame the discussion and introduce the panelists. Ben Lawson briefly summarized the most significant problems affecting modern science and how they limit discovery, stifle innovation, and reduce quality. The remaining panelists then provided brief opening remarks in response to Lawson's summary. Specifically, Frank Durso addressed how the current research and funding environments affects student training and career advice. Peter Hancock addressed how risk-averse sponsors and business models prohibit innovative research. Scott Shappell discussed how different Human Factors and Ergonomics (heretofore referenced as HF/E) career paths lead people to and from their roles as scientists. Specifically, he discussed how to prepare students for flexibility in the changing landscape of the business of science. The panel then turned to facilitated discussion with panelists and audience members. Specific themes included the business of science in relation to educational practices, the applied nature of HF/E training within the scientist/practitioner model, and implications of short-term funding schedules on education and research practices. The panel concluded by discussing how HF/E scientists/practitioners may be uniquely qualified to offer potential solutions to the above problems from educational and systemic perspectives.